Pertanggungjawaban Pidana Debt Collector dan Korporasi: Tinjauan Terhadap Pelanggaran Hukum dalam Penagihan Hutang - Nurhalifah, Dita (UM Purwokerto Press, 2024)
The problem that occurs is the unclear relationship between creditors, namely online loans, and debt collectors, which gives rise to public complaints about debt collection practices by debt collectors who often violate the law. Criminal acts committed by debt collectors in debt collection can be subject to criminal sanctions based on applicable laws, such as the Criminal Code and the ITE Law. Fintech companies as corporations can also be held criminally responsible for the actions of debt collectors working on their behalf. The aim of this research is to find out the responsibility of debt collectors and corporations for criminal acts committed by debt collectors in carrying out debt collection practices. This research uses a normative juridical approach by analyzing library materials and secondary data, such as journals, books and statutory regulations.